SPATA: Strong Pseudonym-Based AuthenTicAtion in Intelligent Transport System - Qazi Ejaz Ali; Naveed Ahmad; Abdul Haseeb Malik; Gauhar Ali; Muhammad Asif; Muhammad Khalid; Yue Cao (IEEE Access)
Intelligent transport system (ITS) is generally deployed to improve road safety, comfort, security, and traffic efficiency. A robust mechanism of authentication and secure communication is required to protect privacy and conditional resolution of pseudonyms to revoke malicious vehicles. In a typical ITS framework, a station can be a vehicle, road side unit, or a server that can participate in communication. During authentication, the real identity of an intelligent transport system station, referred to as a vehicle, should not be revealed in order to preserve its privacy. In this paper, we propose a Strong Pseudonym-based AutenTicAtion (SPATA) framework for preserving the real identity of vehicles. The distributed architecture of SPATA allows vehicles to generate pseudonyms in a very private and secure way. In the absence of a distributed architecture, the privacy cannot be preserved by storing information regarding vehicles in a single location. Therefore, the concept of linkability of certificates based on single authority is eliminated. This is done by keeping the real identity to pseudonym mappings distributed. Furthermore, the size of the certificate revocation list (CRL) is kept small, as only the most recent revoked communication pseudonyms are kept in the CRL. The privacy of the vehicle is preserved during the revocation and resolution phase through the distributed mechanism. Empirical results show that SPATA is a lightweight framework with low computational overhead, average latency, overhead ratio, and stable delivery ratio in both sparse and dense network scenarios.